The Perspective of the People on the Settlement of Criminal Cases Through Penal Meditation at Parepare City - Ni'matul Ilmu Tahir; Zainal Said; Saidah Saidah (DELICTUM : Jurnal Hukum Pidana Islam, 2022)
This study discusses the public perception of criminal cases through penal mediation in the perspective of jināyah fiqh in the city of Parepare. crime in the perspective of jināyah fiqh. This study uses a descriptive qualitative method that uses a normative and juridical theological approach, while the data sources in this study come from primary data, namely police reports from the Parepare Police and secondary data, namely data relating to documents, books, journals and others. The data collection techniques of this research are in the form of case studies, interviews and documentation. Criminal cases that occurred in Parepare City were caused by perception target factors, namely in the form of events, ways of thinking, and actions as well as public perceptions of criminal cases that were resolved through penal mediation so that it had a positive impact on the community because it was easy to do, benefited all parties, and the process implementation is not long.